Status and Factors of Cognitive Function Among Older Adults in Urban China - Shen, Lei; Tang, Xiaochen; Li, Chunbo; Qian, Zhenying; Wang, Jijun; Liu, Wei (Frontiers in Psychology, 2021)
The present study aimed to examine the current status and influencing mechanisms of different demographic factors associated with cognitive function in urban elderly Chinese. A total of 644 older adults from 14 communities in urban China (e.g., Shanghai, Beijing, Wuxi) were investigated by using the Mini-Mental State Examination (MMSE) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). The results indicated that the overall cognitive function in the urban elderly Chinese population was normal. We found an aging effect on cognitive level, and cognitive function declined more rapidly after age 80. Older age, unmarried status, and lower occupational cognitive requirements increased the likelihood of cognitive risk. Higher educational levels and active engagement in exercise may contribute to cognitive reserve and have a protective effect on cognitive decline in late life. Further study is needed to develop appropriate interventions to improve the mental health of urban elderly individuals.